Teredinibacter turnerae secretome highlights key enzymes for plant cell wall degradation - Lyle Ijssel P. De Guzman; Renato C. Carpina; Joan Catherine A. Chua; Eizadora T. Yu (Bioresources and Bioprocessing)
Abstract Carbohydrate-active enzymes (CAZymes) are crucial in the sustainable production of fuels and raw materials from recalcitrant plant cell wall polysaccharides (PCWPs). Teredinibacter turnerae, a symbiont of wood-boring shipworms, is a prolific degrader of plant biomass, largely due to the extensive CAZyme repertoire in its genome. To identify key enzymes involved in PCWP utilization, we analyzed the secretomes of T. turnerae E7MBN strain grown on sucrose, major PCWPs (cellulose, xylan, and pectin), and residual rice hull biomass using mass spectrometry-based proteomics. Our results show that T. turnerae E7MBN exhibits minimal enzyme secretion across various carbon sources, where secretomes mostly display similar functional profiles. Enzymatic complexity varied with the substrate, with cellulose-grown secretome being the most complex and comprising the majority of secreted CAZymes. These CAZymes contain domains that primarily target cellulose, hemicellulose, or pectin, notably including multicatalytic enzymes that are consistently found in the secretome and are likely central to biomass degradation. In contrast, the xylan-grown secretome displayed a more specific response, secreting only a single bifunctional hemicellulase, E7_MBN_00081, also identified as a core component of the bacteria’s enzymatic repertoire. Meanwhile, the pectin-grown secretome consists of multiple tonB-dependent receptors, which, along with isomerases, are considered common secretome constituents. E7MBN also demonstrated the capability to utilize rice hull biomass, predominantly secreting proteins previously identified under cellulose. Protein-protein interaction network analysis further revealed functional associations between CAZymes and several uncharacterized proteins, which include CBM-containing redox enzymes and a putative xylan-acting protein, thus offering new insights into their potential role in lignocellulose degradation. Overall, our work contributes to our understanding of enzymatic strategies employed by T. turnerae for PCWP deconstruction and highlights its potential as a promising source of CAZymes for sustainable biomass conversion. Graphical abstract